Association of Dietary and Lifestyle Inflammation Score With Metabolic Syndrome in a Sample of Iranian Adults - Dehghani Firouzabadi, Fatemeh; Jayedi, Ahmad; Asgari, Elaheh; Akbarzadeh, Zahra; Janbozorgi, Nasim; Djafarian, Kurosh; Shab-Bidar, Sakineh (Frontiers in Nutrition, 2021)
Objective: We aimed to evaluate the association between the dietary and lifestyle inflammation score (DLIS) and metabolic syndrome (MetS) and its components in Iranian adults. Design: Population-based cross-sectional study Setting: General adult population living in Tehran, Iran. Subjects: We included 827 adult men and women with an age range of 18-59 years who were referred to health centers in different districts of Tehran, Iran. Dietary intake was assessed by a semi-quantitative food frequency questionnaire with 168 items. The DLIS was calculated based on four components including dietary inflammation score, physical activity, cigarette smoking, and general obesity. Higher DLIS represents a more pro-inflammatory diet and lifestyle. The odds ratio (OR) and 95% confidence interval (CI) of the MetS across quartiles of the DLIS was calculated by using logistic regression analysis, controlling for age, sex, energy intake, marital status, education status, and occupation. Results: A total of 827 participants (31% men) were included, with a mean age of 44.7 ± 10.7 years. The prevalence of the MetS was 30.5%. The DLIS ranged between -2.35 and +3.19 (mean ± SD: 0.54 ± 1.09). There was a significant positive association between the DLIS and odds of MetS (OR fourth vs first quartile: 1.57, 95% CI: 1.01-2.45) in the fully adjusted model. Conclusion: Our results showed a significant positive association between the DLIS and odds of MetS. The results of the present cross-sectional suggested that having a more pro-inflammatory lifestyle can be associated with MetS. More prospective studies are needed to confirm the findings.